The Impact Analysis of Green Bond Issuance on Carbon (CO2) Emissions: Green Finance Transformation in Developed and Developing Countries : Impact Analysis of Green Bond Issuance on Carbon (CO2) Emissions: Green Finance Transformation in Developed and Developing Countries - Wijianto; Prof. Telisa Aulia Falianty, S.E., M.E. (Jurnal Ekonomi Kuantitatif Terapan, 2026)
This study seeks evidence of whether the issuance of green bonds can affect carbon emissions in developed and developing countries. Identifying this link is crucial in reducing emissions and mitigating climate change. However, empirical evidence on the impact of green bonds is often limited because the data year series covers only a few years. Using the Generalized Method of Moments (GMM), the analysis in this study covered dynamic data from 16 countries between 2016 and 2021. The finding shows that the issuance of green bonds significantly impacted carbon emissions in both developed and developing countries. The more green bonds issued, the lower the carbon emissions. The results also show that green bond issuance in developed and developing countries differs. In developed countries, large investment-class issuers within the banking sector primarily benefit from greenium linked to green bonds. Meanwhile, developing countries face barriers to green bond development, including a lack of proper institutional arrangements, minimum volume requirements, and high transaction costs. Aside from addressing these barriers, the government must focus on improving facilities and infrastructure to increase the impact of issuing green bonds in order to transition to a green economy